PENGARUH GERAKAN LITERASI SEKOLAH TERHADAP MINAT MEMBACA BUKU SUMBER PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 9 PEKANBARU - Rahmadhani, Saszlin; Risnawati; Miftahirrizqa; Anuhgra, Yudha Okta (STAI Pelabuhan Ratu, 2024)
This research aimed at testing the influence of school literacy movement toward interest in reading Islamic education resource books at State Senior High School 9 Pekanbaru. It was quantitative research. 936 students at State Senior High School 9 Pekanbaru were the population of this research, and 10% of them or 94 students were the samples. Questionnaire and documentation were the techniques of collecting data. Simple regression analysis was the technique of analyzing data. Based on data analysis result, the probability score of sig 0.001 was lower than the probability score 0.05, or 0.001<0.05, so H0 was rejected Ha was accepted. It meant that the coefficient of regression was significant. There was a significant influence of school literacy movement toward interest in reading Islamic education resource books at State Senior High School 9 Pekanbaru. The contribution of school literacy movement to interest in reading Islamic education resource books was 93.8%, and 6.2% was influenced or explained by other variables.